A Post-Keynesian Response to Piketty's 'Fundamental Contradiction of Capitalism'. Issue 2 (2nd April 2016) - López-Bernardo, Javier; López-Martínez, Félix; Stockhammer, Engelbert
ABSTRACT: In Capital in the Twenty-First Century, Thomas Piketty presents a rich set of data that deals with income and wealth distribution, output-wealth dynamics and rates of return. He also proposes some 'laws of capitalism'. At the core of his argument lies the 'fundamental inequality of capitalism', an empirical regularity stating that the rate of return on wealth is greater than the growth rate of the economy. This simple construct allows him to conclude that increasing wealth (and income) inequality is an inevitable outcome of capitalism. While we share some of his conclusions, we will highlight some shortcomings of his approach based on a Cambridge post-Keynesian growth-and-distribution model. The paper makes four points. First, r > g is not necessarily associated with increasing inequality in functional distribution. Second, Piketty succumbs to a fallacy of composition when he claims that a necessary condition for r > g is that capitalists save a large share of their capital income. Third, post-Keynesians can learn from Piketty's insights about personal income distribution and incorporate them into their models. Fourth, we reiterate the post-Keynesian argument that a well-behaved aggregate production function does not exist and cannot explain income distribution.